Preferensi Tamu Terhadap Pelayanan Tata Graha Pada Masa Pandemi Covid-19 di Hotel X Nusa Dua, Bali - Putra, Putu Erik Sutrisna; Adi, Ida Ayu Sri Puspa; Sunarsa, I Wayan (Institut Agama Hindu Negeri Gde Puda Mataram, 2022)
The purpose of this study was to determine guest preferences for housekeeping services during the covid-19 pandemic at X Hotel Nusa Dua, Bali. This research was conducted on guest reviews on online travel agents and online interviews with the Training Manager. The type of data used is qualitative data, namely reviews of guest preferences for housekeeping services during the covid-19 pandemic. The data source used is secondary data, namely guest reviews of housekeeping services during the covid-19 pandemic at online travel agents such as TripAdvisor and Booking.com. The data analysis technique used in this study is descriptive qualitative, namely grouping guest reviews on online travel agents with details according to time of stay, range of score, score classification, aspects of reviews based on CHSE, interpreting guest preferences according to data available on online travel agents, analysing preferences in the form of the most preferred and the least preferred reviews. The results of this study will show the housekeeping services that are liked by guests and which are not liked by guests during the covid-19 pandemic at X Hotel Nusa Dua, Bali.